Care and cost consequences of pediatric whole genome sequencing compared to chromosome microarray. (December 2017) - Hayeems, Robin; Bhawra, Jasmin; Tsiplova, Kate; Meyn, M.; Monfared, Nasim; Bowdin, Sarah; Stavropoulos, D.; Marshall, Christian; Basran, Raveen; Shuman, Cheryl; Ito, Shinya; Cohn, Iris; et al.
Abstract The clinical use of whole-genome sequencing (WGS) is expected to alter pediatric medical management. The study aimed to describe the type and cost of healthcare activities following pediatric WGS compared to chromosome microarray (CMA). Healthcare activities prompted by WGS and CMA were ascertained for 101 children with developmental delay over 1 year. Activities following receipt of non-diagnostic CMA were compared to WGS diagnostic and non-diagnostic results. Activities were costed in 2016 Canadian dollars (CDN). Ongoing care accounted for 88.6% of post-test activities. The mean number of lab tests was greater following CMA than WGS (0.55 vs. 0.09;p = 0.007). The mean number of specialist visits was greater following WGS than CMA (0.41 vs. 0;p = 0.016). WGS results (diagnostic vs. non-diagnostic) modified the effect of test type on mean number of activities (p < 0.001). The cost of activities prompted by diagnostic WGS exceeded 557CDN for 10% of cases. In complex pediatric care, CMA prompted additional diagnostic investigations while WGS prompted tailored care guided by genotypic variants. Costs for prompted activities were low for the majority and constitute a small proportion of total test costs. Optimal use of WGS depends on robust evaluation of downstream care and cost consequences.